Intercultural communication competence among higher education international students: a systematic literature review - Xiaoyan, Wang; Syed Zainudin, Sharifah Sofiah; Yaakup, Hani Salwah (Transnational Press London, 2024)
The intercultural communication competence of higher education international students is critical in the multiple culture environment. Understanding how international students improve their intercultural communication competence is vital for providing effective training and teaching in higher education. However, there is a lack of systematic literature reviews on this topic, especially in quantitative methods. This study was dedicated to performing an exhaustive review of existing literature following the PRISMA-SCR guidelines. The findings revealed the absence of a consistent definition and measurement framework for ICC, which complicates the synthesis of research findings and the development of effective educational strategies. The implications of these findings are substantial for educational practices and policy development. They point towards the necessity of creating inclusive and empirically grounded ICC training programs, integrating ICC into international education policies, and providing comprehensive support for the cultural adaptation of international students.